The effect of e-commerce service quality factors on customer satisfaction, purchase intention, and actual purchase in Uzbekistan - Veronika Lee; Seungwook Park; Donhee Lee (Global Business & Finance Review (GBFR), 2022)
Purpose: The purpose of this study is to analyze the impact of characteristics of the service quality of e-commerce platforms on customer satisfaction and purchase intention. Design/methodology/approach: The proposed research model and a set of hypotheses were developed and tested using structural equation modeling based on data collected from 172 e-commerce users in Uzbekistan. Findings: The findings of this study revealed that while the responsiveness of e-commerce platforms is non-essential, website design, reliability, perceived usefulness, and perceived ease of use are essential elements for customer satisfaction in e-commerce. The results indicated that website design, perceived usefulness, and customer satisfaction positively affect purchase intention for e-commerce platforms in Uzbekistan. Research limitations/implications: The study provided that COVID-19 significantly impacted the development and acceptance of e-commerce platforms in Uzbekistan. The results of this study suggested practical insights for improving customer satisfaction and service quality on e-commerce platforms in Uzbekistan. Originality/value: Uzbekistan is a developing country with great potential; however, until recently, little research has been conducted on the Uzbek e-commerce market. From this perspective, this study fills this gap by analyzing the relationship among service quality, technology acceptance factors, customer satisfaction, and purchase intention by applying the initial TAM model. Therefore, it is essential to determine the key factors for improving e-commerce service quality.
Keywords: 650; Customer satisfaction; Service quality; Technology Acceptance Model (TAM); e-commerce; Uzbekistan